PERAN UNIT PELAKSANA TEKNIS PERPARKIRAN DINAS PERHUBUNGAN KOTA PEKANBARU DALAM PEMBINAAN DAN PENGAWASAN PARKIR DI KOTA PEKANBARU - Tomi Ahmad Badawai; Isril ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Handling of roadside parking is a problem in the community where parking rules have not been implemented and implemented properly because there has not been regular guidance and supervision of parking in the city of Pekanbaru so that it has an impact on the community and revenues for the region's original income. Pekanbaru is still found to have parking violations through the Pekanbaru City Parking Technical Implementation Unit as an implementing element of parking handling, of course, carrying out parking handling cannot be separated from guidance and supervision so that roadside parking activities in Pekanbaru City run according to applicable regulations. The purpose of this study was to determine the inhibiting factors for the Parking Technical Implementation Unit of the Pekanbaru City Transportation Service in the Guidance and Supervision of Parking in the City of Pekanbaru. The research method used is a qualitative method with data collection techniques through observation, interviews and documentation. The results of the study show that the guidance and supervision of parking in Pekanbaru City has not been carried out optimally by the Pekanbaru City Parking Technical Implementation Unit where there are still parking officers who have not applied parking retribution fees in accordance with applicable regulations, there are no strict sanctions for illegal parking users, there are no activities data collection and supervision for every parking lot in the city of Pekanbaru, causing concern for the parking service user community. However, the authors suggest that the Pekanbaru City Parking Technical Implementation Unit conducts guidance and supervision of parking activities, collects data and supervises parking locations in Pekanbaru City every working day, provides strict sanctions for parking officers who violate the rules, especially increasing parking fees, and imposes sanctions. for parking attendants who do not wear parking uniforms and parking tickets, as well as collaborating with the community in accommodating community input suggestions regarding parking in Pekanbaru City. Keywords: Role, Retribution, Parking